The Process of Cultivating Anti-Corruption Education Through Saminism Teachings in the Sikep Community in Blora - Atmaja , Diaz Kusuma; Karsidi, Ravik; Sunesti, Yuyun (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to analyze the process of cultural communication in cultivating anti-corruption education through the teachings of Saminism in the Sikep community of Blora Regency. Saminism encompasses values such as honesty, simplicity, responsibility, and the prohibition against infringing on the rights of others, which align with the principles of anti-corruption education. This research uses a qualitative approach with a cultural communication perspective to understand how values are conveyed, interpreted, and transmitted. Data were collected through observation, interviews, and documentation of the Sikep community’s daily life. The results show that cultural communication occurs through interpersonal communication conducted by parents and community leaders. Messages are delivered in the form of pitutur (advice), everyday language, and role modeling. The communication media are traditional and non-formal through family interactions and daily habits. Cultural communication and symbolic interactionism analysis show that anti-corruption values are internalized through repeated social practices and become collective habits passed down through generations, forming shared awareness of honesty and responsibility.